Analisis Prosedur Pembiayaan Pada PT. Woori Finance Cabang Sidoarjo - Patricio Rizal Athallah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the financing procedures implemented at PT Woori Finance Indonesia Sidoarjo Branch and to examine their relationship with civil law aspects, particularly in terms of contractual agreements, prudential principles, and the resolution of non-performing financing. This research applies an empirical juridical method with a descriptive-analytical approach, combining field observations conducted during the internship program with a review of relevant legal regulations and literature. The findings indicate that the financing procedures are carried out through several structured stages, including application submission, data verification, creditworthiness analysis, approval, and fund disbursement. In practice, the company applies the prudential principle through the 5C analysis (character, capacity, capital, collateral, and condition) to minimize potential risks. From a legal perspective, each financing activity establishes a binding legal relationship between the creditor and the debtor, as regulated under civil law provisions. In cases of default, the resolution mechanism is conducted in stages, starting with persuasive and non-litigation approaches before proceeding to further legal actions if necessary. Therefore, financing procedures not only represent administrative processes but also involve significant legal implications that require careful implementation.